High-carbohydrate diet-induced metabolic disorders in Gerbillus tarabuli (a new model of non-alcoholic fatty-liver disease). Protective effects of 20-hydroxyecdysone. (4th March 2021) - Agoun, Hadjer; Semiane, Nesrine; Mallek, Aicha; Bellahreche, Zineb; Hammadi, Soumia; Madjerab, Maha; Abdlalli, Mohamed; Khalkhal, Ali; Dahmani, Yasmina
Abstract: The aim of our study was to reveal the effects of long-term consumption of a high-carbohydrate diet (HCD) on metabolic dysfunctions and histopathological liver alterations in Gerbillus tarabuli, as well as to assess the preventive effects of 20-hydroxyecdysone (20E) in the same animals. Contrary to control diet, HCD induces several metabolic disorders including increased adiposity, dyslipidemia, ectopic fat deposition in the liver, associated with higher levels of plasma AST and ALT. These gerbils showed enhanced oxidative stress with liver damages characteristic of steatohepatitis development. By contrast, adding 20E to HCD resulted in a dose-dependent reduction of all changes induced by HCD. In addition, the hepatoprotective effect of 20E was demonstrated by decreased plasma concentrations of AST, ALT and of hepatic malondialdehyde. Our results suggest that G. tarabuli represents a good model to study diet-induced metabolic disorders and hepatic dysfunctions. Moreover, they demonstrate the efficacy of 20E treatment to counteract the damaging effects of HCD.